Concepções cotidianas e científicas sobre competição na educação de jovens e adultos - GOMES, Jeedir Rodrigues de Jesus (2006)
This study intends to comprehend the role performed by the occurring classroom environment interactions along the process of construction of individual concepts for competition. I have proposed for the present investigation: the characterization and comparison of competition conceptions already attained by every student before and while and after they attended at Ecological Interactions classes; the analysis of some students concepts construction process from the classroom interactions among students themselves as well as between students and the teacher; the comparison of the students previous conceptions, in different moments; the analysis by comparison of the different written answers to all presented questions; evaluation of the interactions contribution to the conceptual elaboration expressed by four students in one of the groups, considering the mutual interactions among students as much as the interaction occurred among students and myself as a Science teacher, along a given didactical sequence. The analysis of the answers to the first questionnaire (preexamination 01) provided material for a second data collection instrument (preexamination 02). The answers to that second questionnaire were arranged in different categories and then compared to the answers given to a third questionnaire (pos-examination 02). The study took place along Science lessons offered to a thirdlevel EJA (Portuguese acronym for Young and Adult Education Program) group of students, in a given State Elementary School. The whole group comprised sixteen students which were involved in every step of the investigation process. From that group there were nine female and seven male students. The classroom events were videotaped and also recorded on audio common tapes. After transcriptions, the analysis proceedings took as a criterion for the selection of valid episodes, the way by which in distinct moments (individually first, then in spontaneously-formed groups, then recombined groups, and individually again) four individuals, from the recombined group 1, constructed individually or during teacher-students-teacher interactions a consensual written answer to the following question: By comparison of the different video scenes shown to you, do you think are there any similarities among the different animal relationships you observed in the scenes? Why? The results brought forth evidences that: from the whole group of sixteen students who took part in every step of the process, nine individuals showed improvement on their previous conceptual profile and seven individuals presented final answers to be ranked under the same category as their initial answers. From those seven students, three of them had their answers ranked under advanced-D category; two individuals, under intermediary categories B and C; and the two last ones, under A category, the farthest category away from a competitions scientific conception. The four selected students proved themselves able to come, after all, to an acceptable generalization to the proposed question, starting from explanations sometimes founded on generalizations or on explanations which comprised theoretical expressions, with or without conceptual apprehension, so proving that they absorbed or processed differently the elements presented in the answers given by the groups of which they were part.